2019
DOI: 10.48550/arxiv.1908.06062
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adversarial shape perturbations on 3D point clouds

Abstract: The importance of training robust neural network grows as 3D data is increasingly utilized in deep learning for vision tasks, like autonomous driving. We examine this problem from the perspective of the attacker, which is necessary in understanding how neural networks can be exploited, and thus defended. More specifically, we propose adversarial attacks based on solving different optimization problems, like minimizing the perceptibility of our generated adversarial examples, or maintaining a uniform density di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…Adversarial Point Clouds. There exist a few studies on adversarial attacks and defenses for point cloud classification [30,13,12,31,27]. For instance, Xiang et al [30] first suggested an optimisation algorithm based on C&W framework [16] using the Chamfer and Hausdorff distance.…”
Section: D Deepmentioning
confidence: 99%
See 3 more Smart Citations
“…Adversarial Point Clouds. There exist a few studies on adversarial attacks and defenses for point cloud classification [30,13,12,31,27]. For instance, Xiang et al [30] first suggested an optimisation algorithm based on C&W framework [16] using the Chamfer and Hausdorff distance.…”
Section: D Deepmentioning
confidence: 99%
“…Several works suggest viable perturbation techniques on point clouds. For instance, adversarial point clouds can be generated by perturbing points individually [30] or in bundles [30,12,31]. It is also possible to mix newly added points with perturbed points in a point cloud to make an adversarial example [12].…”
Section: D Deepmentioning
confidence: 99%
See 2 more Smart Citations
“…[44,36] proposed saliency-based approaches for removing points. Several structured methods have been also introduced to perturb point clouds with the goal of preserving physical fidelity [23].…”
Section: Point Cloud Attacksmentioning
confidence: 99%